2013
DOI: 10.25100/socolen.v39i2.8237
|View full text |Cite
|
Sign up to set email alerts
|

Natural parasitism of Braconidae and Ichneumonidae (Hymenoptera) on Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: Parasitoids Hymenoptera of the families Braconidae and Ichneumonidae were collected, also was determinate their natural parasitism on fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) in the Durango valley region, Mexico. The Braconids species found were: Chelonus insularis (= texanus), Ch. cautus and two species of Meteorus sp., and of Ichneumonidae: Pristomerus spinator and Campoletis sonorensis. In the spring-summer cycle 2012, were collected 1,600 larvae at four locations within the region with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Biological control provided by the natural enemies of D. arcanella presented a strong positive correlation with the population of the pest insect and a negative correlation with the temperature; this agrees with studies that report that these biological control agents respond quickly to changes in the population dynamics of their host and to climatic variations [30,33]. Additionally, parasitoid insects from the Braconidae, Chalcididae, and Ichneumonidae families have been reported as important biological controllers not only in the Depressariidae family but also in other Lepidoptera [22,[34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 87%
“…Biological control provided by the natural enemies of D. arcanella presented a strong positive correlation with the population of the pest insect and a negative correlation with the temperature; this agrees with studies that report that these biological control agents respond quickly to changes in the population dynamics of their host and to climatic variations [30,33]. Additionally, parasitoid insects from the Braconidae, Chalcididae, and Ichneumonidae families have been reported as important biological controllers not only in the Depressariidae family but also in other Lepidoptera [22,[34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 87%
“…(González-Maldonado et al 2014), with an average of 23% parasitism. Also at high elevations in Durango, García-Gutiérrez et al (2013) found parasitism rates up to 44.5% by C. sonorensis . Campoletis spp.…”
Section: Prospects For the Cbc Of S Frugiperdamentioning
confidence: 99%
“…However, the number, identity, and respective distribution of Campoletis species attacking S. frugiperda remain unclear and, therefore it is not possible to provide definite assessments of their climatic suitability. They are often abundant at high elevations, e.g., in Mexico ( García-Gutiérrez et al 2013 , González-Maldonado et al 2014 ). Cam poleti s grioti is the main parasitoid of S. frugiperda in subtropical Argentina, where pest populations are transient and, thus, may be suitable for climatically similar regions in other continents.…”
Section: Prospects For the Cbc Of S Frugiperdamentioning
confidence: 99%
“…From ten years to date in Durango, Mexico, studies have been carried out that have made it possible to know the taxonomic diversity of parasitoids of FAW of the families: Ichneumonidae (Pristomerus spinator Fabricius, Campoletis sonorensis Cameron) [25], Encyrtidae (Euplectrus plathypenae Howard), Tachinidae (Lespesia aletiae Riley, L. archippivora Riley, Winthemia deilephilae Osten Sacken, y Archytas marmoratus Townsend) [26], Trichogrammatidae (Trichogramma pretiosum Riley y Trichogramma exiguum Pinto y Platner) and Scelionidae (Telenomus remus Nixon) [27], and of the family Braconidae subfamily Homolobinae (Homolobus truncator Say) [28], from this same family Ch. insularis, Ch.…”
Section: Diversity Of Fall Armyworm Parasitoidsmentioning
confidence: 99%